Effects of parameter adjustment on the electromagnetic field of an overhead power transmission line model - Sharin Ab Ghani; Mohd Shahril Ahmad Khiar; Imran Sutan Chairul; Nor Hidayah Rahim; Syahrun Nizam Md Arshad@ Hashim (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Studies have shown that high-voltage power transmission lines emit electromagnetic radiation, which has adverse effects on human health. This paper presents the effects of parameter adjustment on the electric and magnetic fields of an overhead power transmission line model at human height. A finite element software, COMSOL multiphysics, was used to simulate the electric and magnetic fields. The electric and magnetic fields generated by the 1200-kV and 220-kV overhead power transmission line models were first computed and the models were validated by comparing the simulation results with those of previous studies. Numbers of parameter were adjusted in order to investigate their effects on the electric and magnetic field distributions. Based on the results, the electric field intensity increases with an increase in the voltage of the conductors. The magnetic field density increases with an increase in the current carried by the conductors. A voltage of 700 kV results in an electricity field intensity that exceeds the residential safety limit (50 kV/m) set by the International Commission on Non-Ionizing Radiation Protection. Hence, a proper right-of-way is needed to ensure that residential areas are at a safe distance away from transmission towers.